Noninvasive Assessment of Atrial Fibrillation Complexity in Relation to Ablation Characteristics and Outcome - Meo, Marianna; Pambrun, Thomas; Derval, Nicolas; Dumas-Pomier, Carole; Puyo, Stéphane; Duchâteau, Josselin; Jaïs, Pierre; Hocini, Mélèze; Haïssaguerre, Michel; Dubois, Rémi (Frontiers in Physiology, 2018)
Background The use of surface recordings to assess atrial fibrillation (AF) complexity is still limited in clinical practice. We propose a noninvasive tool to quantify AF complexity from body surface potential maps (BSPMs) that could be used to choose patients who are eligible for AF ablation and assess therapy impact. Methods BSPMs (mean duration: 7±4 s) were recorded with a 252-lead vest in 97 persistent AF patients (80 male, 64±11 years, duration 9.6±10.4 months) before undergoing catheter ablation. Baseline cycle length (CL) was measured in the left atrial appendage. The procedural endpoint was AF termination. The ablation strategy impact was defined in terms of number of regions ablated, radiofrequency delivery time to achieve AF termination, and acute outcome. The atrial fibrillatory wave signal extracted from BSPMs was divided in 0.5-s consecutive segments, each projected on a 3D subspace determined through principal component analysis (PCA) in the current frame. We introduced the nondipolar component index (NDI) that quantifies the fraction of energy retained after subtracting an equivalent PCA dipolar approximation of heart electrical activity. AF complexity was assessed by the NDI averaged over the entire recording and compared to ablation strategy. Results AF terminated in 77 patients (79%), whose baseline AF CL was 177±40 ms, whereas it was 157±26 ms in patients with unsuccessful ablation outcome (p=0.0586). Mean radiofrequency emission duration was 35±21 min; 4±2 regions were targeted. Long-lasting AF patients (≥12 months) exhibited higher complexity, with higher NDI values (≥12 months: 0.12 ± 0.04 vs <12 months: 0.09 ± 0.03, p<0.01) and short CLs (<160 ms: 0.12 ± 0.03 vs between 160 and 180 ms: 0.10 ± 0.03 vs >180 ms: 0.09 ± 0.03, p<0.01). More organized AF as measured by lower NDI was associated with successful ablation outcome (termination: 0.10 ± 0.03 vs no termination: 0.12 ± 0.04, p<0.01), shorter procedures (<30 min: 0.09 ± 0.04 vs ≥30 min: 0.11 ± 0.03, p<0.001) and fewer ablation targets (<4: 0.09 ± 0.03 vs ≥4: 0.11 ± 0.04, p<0.01). Conclusions AF complexity can be noninvasively quantified by PCA in BSPMs and correlates with ablation outcome and AF pathophysiology.